Automatized Approach to Assessment of Degree of Delamination around a Scribe - Doležel, Petr; Rozsíval, Pavel; Rozsívalová, Veronika; Tvrdík, Jiří (Springer International Publishing AG, 2018)
The aim of this paper is to select a suitable methodology and a sequence of procedures for assessment of degree of delamination around a scribe. This should be achieved with as high level of automation as possible. To keep the universality of application, regulation ISO 4628-8:2007 was followed. The procedure proposed in the paper implements an optical device for data acquisition and two approaches of image processing. It also provides a possibility of manual correction of the results to maintain the robustness of the solution. The preliminary evaluations of the results indicate, that more than 90 % of the samples are interpreted correctly without any human operator interactions.
Automatizovaný přístup ke stanovení stupně delaminace podél řezu
Keywords: Delamination; Optical System; Image Processing; ISO 4628; Delaminace; optický systém; zpracování obrazu; ISO 4628-8:2007